Anti-tumor promoting activity of selected agricultural industrial wastes - Ahmad Raus, Raha; Shamsuddin, Syamsa Syazwan; Muhammad, Muhammad Haziz (2008)
In this study, anti-tumor promoting activity against breast cancer cells (MCF7) of rice and palm oil industrial wastes crude extract was investigated. Methanol and water extracts of both agriculture industrial wastes were tested using MTT assay. The most active extract for inhibition of the proliferation of breast cancer cell was aqueous extract of rice mixture wastes. None of the palm oil industrial wastes showed significant antitumor promoting activity except for the methanolic extract of palm leaf waste. With respect to these results, several of the agriculture industrial wastes could be studied further for their potential to treat breast cancer cells.